Synthesis and Crystal Structure of Aminium 2-(Carbonyl)-3,4,5,6-tetrabromobenzoate 3,4,5,6-Tetrabromobenzene-1,2-dioic Acid Propanone Monosolvate - Li, Jian (Asian Journal of Chemistry, 2012)
The compound aminium 2-(carbonyl)-3,4,5,6-tetrabromobenzoate 3,4,5,6-tetrabromobenzene- 1,2-dioic acid propanone monosolvate (C19H13Br8NO9, Mr = 1038.58) was synthesized and characterized by single crystal X-ray diffraction. The crystal belongs to monoclinic, space group C2/c, with a = 23.870(2), b = 10.8790(10), c = 12.2069(13) Å, b = 107.186(2)º, V = 3028.4(5) Å3, Z = 4, Dc = 2.278 g/cm3, l = 0.71073 Å, μ(MoKa) = 10.638 mm-1, F(000) = 1944. The final refinement gave R = 0.1176, wR(F2) = 0.2719 for 7,196 observed reflections with I > 2s(I). The asymmetric unit of the title compound contains one aminium cation, one 2-(carbonyl)-3,4,5,6- tetrabromobenzoate anion, one 3,4,5,6-tetrabromobenzene-1,2-dioic acid molecule and one propanone molecule. In the anions, the mean planes of the carbonyl and carboxylate groups form dihedral angles of 68.1(3) and 62.7(3)º, respectively with the benzene ring. In the crystal, intermolecular N-H···O, N-H···Br and O-H···O hydrogen bonds connect the components of the structure to form a two-dimensional network.